Recent development of samples' surface properties using scanning ion conductance microscopy. (26th June 2019) - Li, Zhenhui; Xu, Ke; Wei, Fanan
Abstract : Scanning ion conductance microscopy has a widespread application in imaging non‐conductive substrates, especially biological samples due to its high‐resolution and non‐contact imaging. In this work, state‐of‐the‐art achievements on exploring samples' surface properties including surface morphology, sample conductivity and dynamics using scanning ion conductance microscopy are firstly introduced, which confirm that scanning ion conductance microscopy is such a mature technology that realises non‐invasive and high‐resolution imaging. Then, combinations with scanning electrochemical microscopy and atomic force microscopy are demonstrated, which realise the multifunction of scanning ion conductance microscopy. Furthermore, improvements that can help enhance the imaging rate are presented. Finally, the future direction of scanning ion conductance microscopy is discussed.